Unleashing rhizobacteria for sustainable soil remediation: PGPR roles in heavy metal tolerance, detoxification, and plant productivity - Kaushal, Priya; Pati, Aparna Maitra (Frontiers in Microbiology, 2025)
The United Nations Food and Agriculture Organization (FAO) has projected that by 2050, nearly 90% of the world's soil resources will be at risk due to factors such as erosion, overuse of agrochemicals, and industrial pollution. As soil sustains over 95% of the global food supply, such degradation poses a critical threat to food security and ecosystem stability. Among the myriad environmental pollutants, heavy metals (HMs) like arsenic (As), lead (Pb), cadmium (Cd), and chromium (Cr) stand out as insidious threats to the environment. Addressing this issue demands the adoption of eco-friendly and sustainable remediation strategies. Microbial-assisted bioremediation particularly involving plant growth-promoting rhizobacteria (PGPRs) has emerged as a promising approach to enhance HMs detoxification while supporting plant health and soil recovery. In this review, we compile and critically evaluate current literature on PGPR-mediated bioremediation, with a focus on mechanisms of HMs tolerance and detoxification, the impact of PGPRs on soil health, and their role in promoting plant growth in contaminated environments. Overall, aims of the study is to provide a holistic understanding of microbial strategies for managing HMs pollution in soil–plant systems, offering a sustainable path forward for agricultural productivity and environmental restoration.